Informalization and decent work: Labour's challenge. (April 2016) - Webster, Edward; Joynt, Katherine; Sefalafala, Thabang
This article identifies a growing number of workers falling outside the regulatory net of both the state and the trade union movement in South Africa on the basis of an examination of working conditions among private security guards and survivalist enterprises in the clothing sector. Traditional unions have had limited success in organizing these sectors because of the composition of the workforce as well as the nature of their work. New forms of organization, strategies and sources of power will need to be constructed if labour and its allies are to achieve better working and living conditions for all.